Joint quality of self-piercing riveting (SPR) and mechanical behavior under the frictional effect of various rivet coatings. (October 2020) - Karim, Md Abdul; Jeong, Taek-Eon; Noh, Wooram; Park, Keun-Young; Kam, Dong-Hyuck; Kim, Cheolhee; Nam, Dae-Geun; Jung, Hudson; Park, Yeong-Do
Highlights: Friction properties of rivet coatings influences performance of SPR joints. Various rivet coatings need optimization of rivet setting parameters. Higher friction coefficient of rivet coating contributes to higher joint strength. Deformation of rivet coating alters friction properties at rivet/sheet interface. Abstract: This study investigates the frictional influence of different rivet coatings on the joint quality and strength of self-piercing riveted aluminum alloys. A mechanically plated Zn-Sn-Al (Almac®) and an electroplated Zn–Ni coating were applied to the steel rivets to examine the frictional effect of rivet coatings. The friction properties of the rivet coatings were evaluated using a micro-mechanical surface tester. The results demonstrated that the friction properties of the rivet coatings remarkably influenced both the joint quality after riveting and the mechanical behavior of the joints. Under a similar riveting condition, owing to the lower friction coefficient, the Zn-Ni-coated rivets experienced deeper rivet head penetration and larger interlocking in terms of joint quality compared to those of Almac®-coated rivets with a higher friction coefficient. However, under a similar joint quality with respect to the appropriate riveting parameters, the joints with Almac®-coated rivets exhibited higher lap-shear and cross-tensile loads owing to the higher frictional force at the rivet/sheet interface compared to the joints with Zn-Ni-coated rivets. The surface profiles of the coatings after applying an external load using a micro-mechanical surface tester revealed a larger plastic deformation and subsequently higher delamination of the Almac® coating during the riveting process, which altered the friction properties at the rivet/sheet interface and thereby contributed to the higher lap-shear and cross-tensile loads. A numerical analysis also elucidated a significant effect of the friction coefficient at the rivet/sheet interface on the joint quality and lap-shear behavior, which is consistent with the experimental results.